The Power of Zakat in Contemporary Development: How Islamic Philanthropy Alleviates the Economic Impact of Toll Road Projects on MSMEs - Isnaini Harahap; Chuzaimah Batubara; Khairina Tambunan; Abdul Hakim (Faculty of Sharia, IAIN Metro, 2024)
This research examines the impact of toll road construction on Micro, Small, and Medium Enterprises (MSMEs) using Creative Destruction theory and contemporary Islamic philanthropy. The construction of toll roads, although accelerating distribution and accessibility, has had a significant negative impact on MSMEs in various regions. This study explores how MSMEs, particularly in North Sumatra, Pekalongan, and Brebes, are experiencing a decline in income due to reduced vehicle traffic. In addition, this article highlights the role of zakat, infaq, and sadaqah as mechanisms to increase the resilience of MSMEs. This research uses a qualitative approach with observation methods, in-depth interviews, and a literature review, showing that Islamic philanthropy can support the adaptation and sustainability of MSMEs amidst infrastructure changes. The research results show that the negative impact of toll road construction is significant, especially for MSMEs that depend on vehicle traffic, such as dodol in Serdang Bedagai, batik in Pekalongan, and restaurants in Brebes. The turnover decline reached 70-80% in some regions. Many MSMEs were also forced to lay off their employees due to decreased income. However, this study also found that Islamic philanthropic practices such as zakat, infaq, and sadaqah play an important role in increasing the resilience of MSMEs. MSME players who regularly carry out zakat, infaq, and sadaqah can show better adaptation, including product diversification and transition to online business models. Thus, Islamic philanthropy provides short-term assistance and supports long-term positive economic changes for MSMEs.